The relation between intellectual disposition and academic performance of first year dental proper students in the University of the Philippines Manila - Capeding, Leo J. (Philippine Journal of Counseling Psychology, 2006)
This study investigated the relation between intellectual disposition as measured by the Omnibus personality Inventory (OPI), and academic performance as measured by 1st and 2nd semester grades in dental school. The intellectual disposition scales are: thinking introversion (TI), theoretical orientation (TO), estheticism (ES) and complexity (CO). The sample were fifty (50) students accepted into the dental proper program. Results of correlational analysis among the study variables show a generally low and negative correlation coefficients, except for the estheticism scale and Anatomy 12D grade, and estheticism and general weighted average (GWA). The findings suggest that generally, the intellectual dispositions are not related with student's performance in the following subjects: Anatomy; Biochemistry; Anatomy 11A; Anatomy 11B; Community Dentistry; Dental Materials; Perspective in Dentistry; and student's GWA. The significant correlations seen between ES and grades in Anatomy (.31) and GWA (.24) suggest the importance of artistic interest in carrying out successfully the academic and clinical requirements in dental school. Further, a preference for reflective thought, scientific thinking, experimental orientation and interest in complex things do not seem to translate into good scholastic performance in dental school.